KORELASI KADAR KOLESTEROL TOTAL DENGAN (HIGH DENSITY LIPOPROTEIN) HDL PADA PENDERITA HIPERTENSI - Agraini, Agraini; Karwiti, Witi; Nurhaliza, Tiara Risma (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Hypertension or high blood pressure is an increase in systolic and diastolic blood pressure above 140/90 mmHg on two measurements with an interval of five minutes in a fairly calm state. Several factors that can influence the occurrence of hypertension include age, genetics, gender, as well as unhealthy behavior, foods containing salt, fat or foods with high cholesterol. Hypertension can cause high cholesterol levels and decreased HDL levels in the blood. Excess cholesterol and decreased HDL will react with other substances and settle in the blood vessels in the arteries, causing plaque or blockages called atherosclerosis. The narrowing of the blood vessels causes the heart to work harder to meet the need for blood to all tissues. Increased cholesterol levels can affect HDL levels in the body's metabolism. If left for a long time, it will stick to the walls of the blood vessels. This study aims to determine the average levels of total cholesterol and HDL and analyze the relationship between total cholesterol and HDL in hypertension sufferers at the Putri Ayu Community Health Center, Jambi City. The research method used was descriptive observational, where the respondents in this study were hypertension sufferers who had total cholesterol and HDL checked with a total of 60 respondents, using the CHOD-PAP and HDL cholesterol checking method using the CHOD-PAP method. Based on the results of the research, it was found that the average total cholesterol level in hypertension sufferers at the Putri Ayu Community Health Center, Jambi City was 217.97 mg/dl, while the HDL level in hypertension sufferers was 47.42 mg/dl. The statistical test results of the Pearson correlation test showed that there was no significant relationship in hypertension sufferers between total cholesterol levels and HDL at the Putri Ayu Community Health Center, Jambi City with a P-Value of 0.310 (>0.05).